Mechanical and dynamic mechanical properties of tyre tread cap compounds based on NR/BR/SBR triblends - Manoj N R; Mohamed P K; Nando Golak B; Varkey T D (Indian Journal of Natural Rubber Research, 1994)
This paper deals with the effect of proportion of styrene-butadiene rubber (SBR) on the static and dynamic mechanical properties of NR/BR/SBR triblends. Attempts have also been made to optimise the accelrator-sulphur system for the blends. The effect of incorporation of a higher structure black with the triblend was also studied. Introducing styrene-butadiene rubber into the mix containing a blend of NR/BR improved static, dynamic as well as age resistance properties. A proportion of 15 phr of SBR was found to impart the best balance of technical properties. Semi-efficient vulcanization system with a sulphur to accelerator ratio of 2:1.2 gave the best balance of technical properties and dynamic mechanical properties for the triblend containing 15 phr of SBR. Increased structure of the carbon black in the mix increased loss modulus but improved flex fatigue properties and abrasion resistance of the triblend.
Keywords: Mechanical properties; Mechanical properties; Natural rubber; Natural rubber; NR/BR/SBR triblend; NR/BR/SBR triblend; Tyre tread compound; Tyre tread compound